2003
DOI: 10.1046/j.1365-2958.2003.03351.x
|View full text |Cite
|
Sign up to set email alerts
|

Acyl‐homoserine lactone acylase from Ralstonia strain XJ12B represents a novel and potent class of quorum‐quenching enzymes

Abstract: SummaryN -acylhomoserine lactones (AHLs) are used as signal molecules by many quorum-sensing Proteobacteria. Diverse plant and animal pathogens use AHLs to regulate infection and virulence functions. These signals are subject to biological inactivation by AHLlactonases and AHL-acylases. Previously, little was known about the molecular details underlying the latter mechanism. An AHL signal-inactivating bacterium, identified as a Ralstonia sp., was isolated from a mixed-species biofilm. The signal inactivation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
409
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 482 publications
(426 citation statements)
references
References 57 publications
9
409
1
7
Order By: Relevance
“…Following this initial report, acylase activity was demonstrated in another betaproteobacterium, a Ralstonia isolate, and the responsible AHL inactivation gene was named aiiD (46). The AiiD protein was most similar to aculeacin A acylase (AAC) from Actinoplanes utahensis but also shared similarity with other acylases responsible for hydrolysis of penicillin and cephalosporin (46). Interestingly, homologues of AiiD were also found in various other Ralstonia and Pseudomonas spp.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 93%
See 4 more Smart Citations
“…Following this initial report, acylase activity was demonstrated in another betaproteobacterium, a Ralstonia isolate, and the responsible AHL inactivation gene was named aiiD (46). The AiiD protein was most similar to aculeacin A acylase (AAC) from Actinoplanes utahensis but also shared similarity with other acylases responsible for hydrolysis of penicillin and cephalosporin (46). Interestingly, homologues of AiiD were also found in various other Ralstonia and Pseudomonas spp.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 93%
“…Interestingly, homologues of AiiD were also found in various other Ralstonia and Pseudomonas spp. (46), and these bacteria were later confirmed to also possess AHL acylase activity (42,44,45,47,51,52). Biochemical analysis of the fate of 3OC10HSL incubated with purified AiiD protein confirmed that AiiD functions as an AHL acylase, releasing HSL and 3-oxodecanoic acid as the major degradation products (46).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 95%
See 3 more Smart Citations